Dendrite growth suppression by Zn2+-integrated nafion ionomer membranes: beyond porous separators toward aqueous Zn/V2O5 batteries with extended cycle life - Ghosh, Meena; Vijayakumar, Vidyanand; Kurungot, Sreekumar (Energy Technology, 2019)
The dendritic/irregular growth of zinc deposits in the anode surface is often considered as a major intricacy limiting the lifespan of aqueous zinc-ion batteries. The effect of separators on the evolution of the surface morphology of the anode/cathode is never thoroughly studied. Herein, for the first time, the efficacy of the Zn2+-integrated Nafion ionomer membrane is demonstrated as a separator to effectively suppress the growth of irregular zinc deposits in the metallic anode of an aqueous Zn/V2O5 battery. The Zn2+-ions coordinated with the SO3- moieties in Nafion result in a high transference number of the Zn2+ cation, all the while facilitating a high ionic conductivity. The Zn2+-integrated Nafion membrane enables the Zn/V2O5 cell to deliver a high specific capacity of 510 mAh g(-1) at a current of 0.25 A g(-1), which is close to the theoretical capacity of anhydrous V2O5 (589 mAh g(-1)). Moreover, the same cell exhibits an excellent cycling stability of 88% retention of the initial capacity even after 1800 charge-discharge cycles, superior to that of the Zn/V2O5 cells comprising conventional porous separators.